Integrated Management of Southern Blight in Vegetable Production - Chenzhao Xie; Gary Vallad (EDIS)
PP272, a 6-page illustrated fact sheet by Chenzhao Xie and Gary Vallad, guides vegetable growers to recognize and manage this serious fungal disease affecting diverse crops grown around the world, especially in tropical and subtropical regions — symptoms and signs, pathogen biology, disease cycle, epidemiology, and integrated management. Includes references. Published by the UF Department of Plant Pathology, March 2010.